Pond fertilization through inorganic sources: an overview - Das, S K; Jana, B B (Indian Journal of Fisheries, 2011)
Input of nutrients through inorganic sources has long been a common practice of pond fertilization. The state of the art of pond fertilization has been reviewed in the present paper. Phosphorus through phosphate fertilizer is the most important nutrient regulating the productivity offish ponds as 1 kg P2Os went into 2.5 to 28.22 kg of carp production under different conditions. In most cases, nitrogen is not considered as a limiting nutrient of pond productivity. Nitrogen may be eliminated from fertilization programme in case of old well fertilised ponds without reducing fish yields, however, there are differences of opinion regarding the importance of nitrogen fertilizer in fish ponds. The ratio of N and P seems to play an important role in limiting the efficacy of nitrogen fertilizers. P limitation of phytoplankton occurs when the N : P ratio of the nutrient supply is substantially higher than the mean atomic ratio of N to P in phytoplan kton cells (15 : 1); an ambient ratio less than 15 : 1 results in N limitation. The role of potassium as fertilizer in the pond culture system has not been properly assessed. As fish pond soils exhibit higher amount of organic mattsr than upland agricultural soils and as the pH of bottom soil and water remains alkaline, availability of potassium in the pond sediment is high. Thus, the concept of pond fertilization should be based on NPC rather than NPK as practised in agricultural soil with less organic matter. Generalised schedule of pond fertilization resulted in high variability of productivity in different agroclimatic areas. Many interacting factors such as soil type, wa;er depth, water retention time, species of culture, quality and quantity of vegetation should be taken into consideration. More studies on pond fertilization in the context of nutrient dynamics and fertilizer-microbial interactions under different agroclimatic regions are necessary for an effective, appropriate and economic fertilization programme. Also, the environmental consequences of overfertilization resulting in pollution and subsequent hazards in public health should be taken into account.